ELECTRONIC WORD OF MOUTH AND ELOQUENCE: AN ANALYSIS OF REVIEWS IN HOSPITALITY SECTOR (IITM Journal of Business Studies, 2024)
With the advent of internet and internet based  media, electronic word of mouth has gained  prominence in influencing consumer decision.  An exploratory study using qualitative analysis  has been conducted in the hospitality industry in  order to understand the trends in the generation  of electronic content in hotel reviews by  customers. Two hundred positive and an equal  number of negative reviews of a top brand hotel  have been explored in the order of appearance in  a popular accommodation website. The analysis  indicated that customers are more eloquent in  describing positive aspects, overall evaluations  and positive overall evaluations than negative  aspects, attribute based evaluations and negative  overall evaluations. Negative evaluations are  more based on specific attributes than overall  evaluations. The adjectives and verbs used in  describing a positive evaluation are found to  be more compared to negative evaluation. The  findings are at variance with some of the earlier  studies. These findings are of practical relevance  to hoteliers in focusing their marketing and  operation efforts.
Keywords: Electronic word of mouth; hospitality; review; eloquence; social media